Analisis Pembangunan Infrastruktur Jalan Terhadap Perkembangan Pariwisata Kawasan Pinggiran Kota - Latifah Nur Hayati (JOURNAL ECONOMICS AND STRATEGY, 2022)
Abstract: This study aims to determine how the influence of road infrastructure development on the development of tourism in suburban areas and regional economic growth. This research was conducted using literature study research, namely by looking for theories and various references that have relevance to the research being carried out by the researcher. The research method used in this research is descriptive qualitative research method, which makes the researcher as the object. Researchers have a role to collect, analyze, and describe all events and possibilities that will occur in the development of Setigi tourism. The data and information used in this study are secondary data obtained by researchers from various kinds of literature studies using internet media in the form of online journals. The results of this study indicate that road infrastructure development plays an important role in the development of tourism in suburban areas (Wisata Setigi), and the development of road infrastructure is also a very important influence on the economic growth of a region. Keywords: Development, Infrastructure, Growth, Economy, Tourism, Roads